The Role of Artificial Intelligence Literacy in Building an Inclusive Digital Society - Zugandi, Rizan Hari (Indonesian Journal of Research and Service Studies, 2024)
The rapid development of Artificial Intelligence (AI) has fundamentally transformed social media from a communication platform into an intelligent digital ecosystem that actively shapes the dissemination of information and public opinion. AI-based technologies, including machine learning, recommendation algorithms, and generative AI, have enhanced content personalization and user engagement while raising concerns about filter bubbles, echo chambers, misinformation, and algorithmic transparency. This study aims to analyze how AI-based social media influences public opinion formation through algorithmic mechanisms, information personalization, digital interactions, and automated content dissemination. A qualitative approach using desk research was employed by systematically reviewing recent scientific literature, academic books, international reports, and policy documents related to AI, social media, and digital communication. Data were analyzed using qualitative content analysis involving data reduction, thematic coding, categorization, synthesis, and critical interpretation. The findings indicate that AI has become a socio-technical infrastructure that significantly influences public opinion by regulating information visibility, reinforcing behavioral preferences, and accelerating the spread of digital narratives. While AI improves communication efficiency and user participation, it also increases the risk of ideological polarization, disinformation, and reduced diversity of information exposure. Therefore, transparent AI governance, ethical implementation, and strengthening digital literacy are crucial for fostering an inclusive, accountable, and democratic digital public sphere.